Managing ecosystem emergence and evolution: Strategies for ecosystem architects - Daymond, Jarryd; Knight, Eric; Rumyantseva, Maria; Maguire, Steven (Strategic Management Journal, 2023)
Abstract Research Summary While the notion of ecosystems has become prominent in scholarly and practitioner strategy literature in recent years, more can be done to bridge these two communities. In this introduction to the SMS Collection, we interrogate strategy scholarship from the perspective of “ecosystem architects,” who are private or public sector actors interested in nurturing and developing a given ecosystem as a whole. In doing so, we collate and discuss key articles published in the journals of the Strategic Management Society which, considered together, shed new light on processes of ecosystem emergence and evolution. We distill a range of insights for ecosystem architect practitioners and outline four strategies for them to create conditions appropriate to their ecosystem and its stage of development. Managerial Summary What insights does strategy research offer to practitioners interested in nurturing the creation and ongoing development of a range of different types of ecosystems? In this introduction to the SMS Collection, we distill relevant findings and outline four strategies for public and private ecosystem architects to create conditions appropriate to their ecosystem and its stage of development. Specifically, we outline approaches to create conditions for coalescence, coopetition, cooperation, and contained contestation within emerging and evolving ecosystems.